(untitled) (Brazilian Journal of Health Research, 2022)
Introduction: The chronic non-communicable diseases are the leading causes of morbidity and mortality in the world, among the most relevant are circulatory system diseases. Objectives: This study aimed to identify deaths from circulatory system diseases in Palmas, Tocantins, in the period from 2011 to 2015. Methods: This is a descriptive, quantitative and ecological study, carried out from the death registries of residents in Palmas, used as a data source the Mortality Information System of the Municipal Health Department. Stratified by: basic cause of death, age, race/color, education, gender and occupation. Data analysis was performed by calculating the mortality coefficient, absolute frequency and proportion using the EpiInfo 7.0 software. Results: 991 deaths due to circulatory system diseases were identified, with no significant variations between 2011 and 2015. The frequency of deaths was higher among male individuals (57.3%), older than 70 years (50.5%), low education (50.6%), main occupation retired/pensioner (28.4%), race/color brown (49.7%) and for ischemic heart diseases (30.6%).Conclusion: There were no significant changes in the mortality coefficient due to circulatory system diseases during the studied period. However, the mortality coefficient increases according to longevity, it becomes evident the necessity to intensify actions based on models of care for the chronic condition, in prevention and health promotion in order to reduce these rates.